Effect of Accounting Information System, System Quality, and Security Quality on Customer Satisfaction of Mobile Banking Users: Pengaruh Sistem Informasi Akutansi, Kualitas Sistem,dan Kualitas Keamanan Terhadap Kepuasan Nasabah Pengguna Mobile Banking - Zubaida, Refiana; Abidin, Fityan Izza Noor (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of Accounting Information Systems, System Quality, and Security Quality on Mobile Banking User Satisfaction. Study on Accounting Students at Muhammadiyah University of Sidoarjo. The analytical tool used is tabulating the questionnaire, collecting data in the form of validity testing and reliability testing. The hypothesis in this study is that there is an effect of Accounting Information Systems, System Quality, and Security Quality on Mobile Banking User Satisfaction. The sampling technique used in this study was purposive sampling with a total sample of 83 respondents. Data analysis used multiple linear regression. The results of the study using the t-test showed that the variables of Accounting Information System, System Quality, and Security Quality separately (partially) had an influence on Mobile Banking user satisfaction. The magnitude of the effect of accounting information system variables, system quality and security quality on customer satisfaction variables is 93.6%. Meanwhile, 6.4% is influenced by other variables besides accounting information system variables, system quality and security quality.